Enhancement of fiber-matrix interface of recycled cotton fibers reinforced epoxy composite for improved mechanical properties. (27th January 2020) - Baccouch, Wafa; Ghith, Adel; Yalcin-Enis, Ipek; Sezgin, Hande; Miled, Wafa; Legrand, Xavier; Faten, Fayala
Abstract: The aim of this study is to enhance the fiber-matrix interface of cotton waste reinforced composite panels by a specific chemical treatment. For this purpose, cotton fibers are treated in sodium hydroxide (NaOH) solution with three different concentrations (0.5 M, 1 M, and 1.5 M) and three different soaking times combinations (1 h, 3 h, and 5 h). Mechanical evaluation of treated and untreated reinforcements and composite panels are characterized using tensile test whereas the chemistries of fiber reinforcements are investigated using Fourier-transform infrared spectroscopy analysis and the fiber-matrix interactions are morphologically examined using scanning electron microscopy. Results indicate a remarkable enhancement in mechanical properties of composites via improving the interfacial adhesion and compatibility between fiber and matrix with a significant increase of Young modulus up to 270% for reinforcements and to 70% for composite materials compared to untreated materials.